1997
DOI: 10.1002/etc.5620160502
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of 2‐mercaptobenzothiazole on microbial growth in a variety of trophic conditions

Abstract: Abstract-2-Mercaptobenzothiazole (MBT) is found mainly in the wastewaters of its industrial production as a rubber vulcanization accelerator. Because this compound was found to be toxic to activated sludges and because it causes poor process performances, its impact on bacteria in particular was studied. 2-Mercaptobenzothiazole, but not other benzothiazoles, exerted mainly bacteriostatic effects towards Escherichia coli, Sarcina lutea, Staphylococcus aureus, and a 2-hydroxybenzothiazole-degrading isolate (OBT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…As a result of MBT manufacture, process waters originate which contain 2-hydroxybenzothiazole (OBT), benzothiazole (BT), and benzothiazole-2-sulfonate (BTSO 3 ), apart from MBT itself. A biological purification of such wastewaters is often considered to be problematic (1,12,13), probably due to the toxic effects ascribed to MBT (5,6,(13)(14)(15). This might explain why only a few benzothiazole-degrading organisms are reported in the literature and why information on benzothiazole degradation pathways is scarce.…”
mentioning
confidence: 99%
“…As a result of MBT manufacture, process waters originate which contain 2-hydroxybenzothiazole (OBT), benzothiazole (BT), and benzothiazole-2-sulfonate (BTSO 3 ), apart from MBT itself. A biological purification of such wastewaters is often considered to be problematic (1,12,13), probably due to the toxic effects ascribed to MBT (5,6,(13)(14)(15). This might explain why only a few benzothiazole-degrading organisms are reported in the literature and why information on benzothiazole degradation pathways is scarce.…”
mentioning
confidence: 99%
“…Among the identified bacterial strains capable of BT and BTA biotransformation, the most common bacteria were Rhodococcus sp., Enterobacter sp., and Arthrobacter sp. In other studies, Rhodococcus strain PA, Rhodococcus OBT18, Rhodococcus erythropolis strain BTSO 3 1, Rhodococcus rhodochrous and Pseudomonas putida strain HKT 554 were tested for BT biodegradation (Gaja & Knapp, 1997;De Wever et al, 1997, El-Bassi et al, 2010Chorao et al, 2009). Rhodococcus strains PA and OBT18 were capable of BT and 2-hydroxybenzothiazole (OBT) degradation, but they did not remove 2-mercaptobenzothiazole (MBT).…”
Section: Identification Of Bt and Bta Degrading Bacteriamentioning
confidence: 99%
“…Indeed, many reports attest to the antimicrobial activities of the quaternary ammonium groups [40,[44][45][46][47] and 2-mercaptobenzothiazole. [48][49][50][51][52] It is demonstrated that quaternary ammonium groups are membrane active [40,47] while 2-mercaptobenzothiazole are shown to function at the level of the cell membrane. [50,51] Previously, we proved that η 6 -dichlorobenzene-η 5 -cyclopentadienyliron(II) complexes are membrane active and also induce oxidative stress on microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52] It is demonstrated that quaternary ammonium groups are membrane active [40,47] while 2-mercaptobenzothiazole are shown to function at the level of the cell membrane. [50,51] Previously, we proved that η 6 -dichlorobenzene-η 5 -cyclopentadienyliron(II) complexes are membrane active and also induce oxidative stress on microorganisms. [42,43] Therefore, we expect these hybrids to function via multiple mechanisms that include generating oxidative stress and interacting with cell membrane and its functions in addition to other yet-to-be identified mechanisms.…”
Section: Introductionmentioning
confidence: 99%